Leasing and factoring companies offering shariah-based financing products in Malaysia: reference to the Financial Services Act 2013 (FSA) and the Islamic Financial Services Act 2013 (IFSA) / Ulfah Mansurah Zainudin and Ahmad Azam Othman - Zainudin, Ulfah Mansurah; Othman, Ahmad Azam (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
Leasing and factoring companies are examples of non-banking financial institutions offering Shariah-based financing products in Malaysia. Since the introduction of the Islamic Financial Services Act 2013 (IFSA) and the Financial Services Act 2013 (FSA), the legal provisions on leasing and factoring companies as scheduled institutions were no longer available as provided in the previous repealed legislation. This raises the issue of relevant legal provisions regulating leasing and factoring companies, especially those offering Shariah-based financing products. This research explores the applicable legal provisions of the FSA and IFSA related to leasing and factoring companies offering Shariah-based financing products. This study uses qualitative methods to analyse pertinent references from both primary and secondary legal sources. Content analysis is applied to these sources to generate findings related to the topic. This research concludes that the FSA and IFSA provide relevant legal provisions for leasing and factoring companies offering Shariah-based financing products. However, there is currently no explicit legal provision that clearly defines the legal standing of leasing and factoring companies offering Shariah-based financing products. Establishing such legal provisions is essential, as they would create a robust legal framework for these companies, fostering transparency and confidence in the market. This clarity would not only support the effective operation of leasing and factoring companies but also facilitate future development within the industry, ensuring that Shariah-compliant products can thrive in a competitive financial landscape.